Acknowledgement of manuscript reviewers the underappreciated contributors - Bakillah, Ahmed (Nutr Metab (Lond), 2016)
We and the Editorial Board sincerely acknowledge and thank all the reviewers for their active participation and contribution during 2015 (Volume 12). We greatly appreciate their dedication and behind the scenes contribution. It is largely due to their support and expertise that we have been able to publish high standard manuscripts. We would also like to thank authors for choosing Nutrition & Metabolism and contributing their cherished work to this journal.